2013
DOI: 10.1590/s1679-87592013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Fish bycatch of the laulao catfish Brachyplatystoma vaillantii (Valenciennes, 1840) trawl fishery in the Amazon Estuary

Abstract: This study aimed to analyse the composition and seasonal variation in the fish bycatch of the Brachyplatystoma vaillantii trawl fishery in the Amazon Estuary in 2009 by monitoring the trips of 48 vessels. The bycatch represented 29% of the catches, totalling 22,228 specimens and 52 taxa, distributed in 22 families (the principal families were Ariidae, Pimelodidae, and Sciaenidae). Brachyplatystoma rousseauxii, Plagioscion squamosissimus, and Sciades herzbergii together contributed 69% of the bycatch and were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…Factors such as environment and fishing gears were the same in both areas and did not influence the difference in catch and follow the pattern of the fisheries in other regions of the Amazon, as reported by Barthem (1999), Batista and Petrere Jr. (2003) and Ruffino (2004) the capture of jatuarana in both studied areas was mainly realized in the channel rivers or on its banks, demonstrating the importance of this environment for the local fisheries. Goulding (1979) observed that the capture of many Characiformes in the Madeira River (including jatuarana) was performed mainly in mouths of tributaries, rivers and the lowland, with catches in rivers occurring mainly during reproductive migration when B. amazonicus was more vulnerable to fishing gear.…”
Section: Resultssupporting
confidence: 73%
“…Factors such as environment and fishing gears were the same in both areas and did not influence the difference in catch and follow the pattern of the fisheries in other regions of the Amazon, as reported by Barthem (1999), Batista and Petrere Jr. (2003) and Ruffino (2004) the capture of jatuarana in both studied areas was mainly realized in the channel rivers or on its banks, demonstrating the importance of this environment for the local fisheries. Goulding (1979) observed that the capture of many Characiformes in the Madeira River (including jatuarana) was performed mainly in mouths of tributaries, rivers and the lowland, with catches in rivers occurring mainly during reproductive migration when B. amazonicus was more vulnerable to fishing gear.…”
Section: Resultssupporting
confidence: 73%
“…Manaus (03°05'39.60''S, 60°01'33.63''W), is the largest city in the central Amazon, located at the confluence of the whitewater Solimões River with the blackwater Negro River. Belém (01°27'18.04''S 48°30'08.90''W), is situated on the banks of the Amazon estuary and is the main landing port of large migratory catfishes fisheries in Brazil [ 30 ]. Prior to otolith collection the total length (TL) and weight (W) of each fish was recorded: dourada: mean TL = 83.6 cm, mean W = 8.58 kg; piramutaba: mean TL = 67.6 cm, mean W = 3.34 kg; piraíba: mean TL = 186.6 cm, mean W = 86.6 kg.…”
Section: Methodsmentioning
confidence: 99%
“…Dourada ( Brachyplatystoma rousseauxii ) is a pelagic predator found throughout the whitewater and clearwater rivers of the Amazon and supports the largest fishery in the Amazon [ 27 , 29 ]. Piramutaba ( Brachyplatystoma vaillantii ) make up a second large export fishery and are found almost exclusively in the Amazon River mainstem, whitewater tributaries, and the estuary [ 30 – 32 ]. Piraíba ( Brachyplatystoma filamentosum ) is the largest of the migratory catfish, present in whitewater rivers throughout the Amazon basin.…”
Section: Introductionmentioning
confidence: 99%
“…Around 16,000 fishers participated in 2005, of which 50% were concentrated in the estuary, where the only industrial Amazon fishery takes place. The industrial fleet uses demersal pair trawls, and mainly targets juvenile Piramutaba, with a bycatch of small Dourada (Jimenez et al 2013). The small-scale fleet operates throughout the Amazon basin, using drifting gillnets (80%) or longlines (20%).…”
Section: Goliath Catfish Amazon River (Brazil) Introductionmentioning
confidence: 99%